FROM PROTECTIONISM TO GLOBALIZATION: THE ONE BELT, ONE ROAD DYNAMICS IN AFRICA - BANWO ADETORO OLANIYI (International Studies Journal)
This study examines the One Belt, One Road Policy of China in Africa with the central aim of depicting the impact of globalization and protectionism. This research work is located within the precincts of globalization and protectionism. Data were obtained through homogenous purpose sampling and content analysis was used to study this work. Certain factors such as globalization, protectionism, trade, barriers and consumers were selected for study in this work. It adopts the theoretical framework of globalization as propounded by Williams I. Robinson who argues that as goods and services get transferred across national borders, their manufacturing and production also get fragmented. It ascertains that globalization allows free trade through broken barriers and it has both positive and negative implications on economies that promote globalization. African economies are bedevilled with ailing industrial sectors and lack of funds to promote capital projects. Should Africa protect its economy and derive the needed capital from trade or should Africa submit to the whims and caprices of China? China is a strong economic ally of most African countries because of trade, infrastructural development and finances. Most African economies are indebted to it, however, the restrictions offered by protectionism promotes the development of industries in Africa as against the huge competition promoted by globalization. While it’s understandable that protectionism offers no innovative potentials, globalization on the other provides global economic growth, job creation, competitive markets and prices. This research work therefore aims to examine the concept of globalization against protectionism, it intends to draw inferences and develop a model that would work for Africans and the Chinese.